Enzymatic Fragment Condensation of Side Chain‐Protected Peptides using Subtilisin A in Anhydrous Organic Solvents: A General Strategy for Industrial Peptide Synthesis. Issue 2 (4th January 2013) - Nuijens, Timo; Schepers, Annette H. M.; Cusan, Claudia; Kruijtzer, John A. W.; Rijkers, Dirk T. S.; Liskamp, Rob M. J.; Quaedflieg, Peter J. L. M.
Abstract Herein, the enzymatic condensation of side chain‐protected peptide fragments using subtilisin A in anhydrous organic solvents is described. A screening with dipeptide Cbz‐Val‐Xxx carboxamidomethyl esters with H‐Xxx‐Val‐NH2 nucleophiles was performed, wherein Xxx stands for every (side chain‐protected) amino acid residue. Finally, it was demonstrated that it is feasible to enzymatically condense larger peptide fragments (up to the 10‐mer level) bearing multiple side chain‐protecting groups with very high conversion.